Program Pembelajaran Bahasa Arab di SMP Plus Al-Aqsha Jatinagor Sumedang - Ulfah Fauziyah Rahmah (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2019)
Al-Aqsa Middle School is a boarding school-based junior high school, which requires all students to stay in a dormitory for three years and speak Arabic and English. Al-Aqsa Middle School graduates can become individuals who are familiar with foreign languages based on language learning routines. This study tries to reveal the Arabic learning system so that students can get used to speaking Arabic. This research is qualitative research using descriptive methods. The code collection techniques used in this study were observation, interviews, and documentation. The purpose of this study is to describe the implementation of learning the Arabic language, knowing the supporting and inhibiting factors, and expressing the abilities of their students. The results of this study indicate that: 1) the implementation of linguistic programs carried out by the Al-Aqsha Middle School language development institution consisting of planning, organizing, implementing, controlling, and evaluating has not been maximally achieved. 2) Factors supporting the implementation of this linguistic program are those of the language instructors in language. The drawing factor is the freedom of communication used between students and traders. 3) The ability of the Arabic language skills of students at Al Aqsha Plus Middle School is not good enough because the program implementation has not been maximized.